Multiple scattering in grazing‐incidence X‐ray diffraction: impact on lattice‐constant determination in thin films. (1st May 2016) - Resel, Roland; Bainschab, Markus; Pichler, Alexander; Dingemans, Theo; Simbrunner, Clemens; Stangl, Julian; Salzmann, Ingo
Abstract : The use of grazing‐incidence X‐ray diffraction to determine the crystal structure from thin films requires accurate positions of Bragg peaks. Refraction effects and multiple scattering events have to be corrected or minimized. Abstract : Dynamical scattering effects are observed in grazing‐incidence X‐ray diffraction experiments using an organic thin film of 2, 2′:6′, 2′′‐ternaphthalene grown on oxidized silicon as substrate. Here, a splitting of all Bragg peaks in the out‐of‐plane direction ( z ‐direction) has been observed, the magnitude of which depends both on the incidence angle of the primary beam and the out‐of‐plane angle of the scattered beam. The incident angle was varied between 0.09° and 0.25° for synchrotron radiation of 10.5 keV. This study reveals comparable intensities of the split peaks with a maximum for incidence angles close to the critical angle of total external reflection of the substrate. This observation is rationalized by two different scattering pathways resulting in diffraction peaks at different positions at the detector. In order to minimize the splitting, the data suggest either using incident angles well below the critical angle of total reflection or angles well above, which sufficiently attenuates the contributions from the second scattering path. This study highlights that the refraction of X‐rays in (organic) thin films has to be corrected accordingly to allow for the determination of peak positions with sufficient accuracy. Based thereon, a reliable determination of the lattice constants becomes feasible, which is required for crystallographic structure solutions from thin films.